Regeneração óssea com hidroxiapatita granulada : estudo experimental em calvária de coelhos - Nogueira, Fabio Pinto (2007)
Objective: The importance of bone regeneration is directly proportional to the difficulty to repair large bone defects. Large bone losses, such as those caused by trauma, infections or tumors, are a great challenge to medical practice. Due to the limited autogenous bone available and difficult utilization of other grafts for medical purposes, the use of substitute materials to fill and repair these losses has been considered. Methods: The present study employed granulated hydroxyapatite in bicortical bone defects in calvarias of New Zealand rabbits. A total of 44 rabbits were used, divided into 32 rabbits in the control group and 12 in the study group. Defects in the control group did not receive any protective barrier. In the study group, granulated hydroxyapatite mixed with blood clot of the wound was placed in calvaria defects. Evaluations were performed at 15, 30, 60 and 120 days postoperatively, by histomorphometry and digital radiographs. Results: Microscopic analysis revealed absence of foreign body inflammatory reaction and formation of osteoid material firmly attached to the surface of hydroxyapatite granules, indicating an osteoconductive process. The digital radiographs revealed formation of bone tissue at 30 days after surgery. It should be highlighted that the granulated hydroxyapatite presented degradation and replacement by autogenous bone. There was formation of immature bone at 15, 30 and 60 days and of mature bone at 30 and 60 days, with p<0.05. Conclusion: This demonstrated the histocompatibility of hydroxyapatite, as well as the properties of filling and mechanical and volumetric stability in critical size bone defect.